HRM, Communication, Satisfaction, and Perceived Performance: A Cross-Level Test. (September 2013) - Den Hartog, Deanne N.; Boon, Corine; Verburg, Robert M.; Croon, Marcel A.
Employee perceptions of HR practices are often assumed to play an important mediating role in the relationship between HR systems and HR outcomes. In a multisource, multilevel study of 2, 063 employees and 449 managers in 119 branches of a single large firm, the authors tested how managers' perceptions of the HR practices implemented in the unit relate to employee perceptions of these HR practices. The authors' main aim is to explore managers' communication quality as a moderator of the relationship between manager-rated and employee-rated HR practices. They also tested whether perceived human resource management (HRM) perceptions in turn relate to perceived unit performance and satisfaction. Multilevel structural equation modeling analyses showed that HRM perceptions mediated the relationship between implemented HRM and both satisfaction and unit performance and that communication moderated the relationship between manager-rated and employee-rated HRM. These findings contribute to scholars' understanding of how HRM affects employee-related outcomes.